Incidence and time trends of anal cancer among people living with HIV in Australia. (1st July 2019) - Jin, Fengyi; Vajdic, Claire M.; Law, Matthew; Amin, Janaki; van Leeuwen, Marina; McGregor, Skye; Poynten, I. Mary; Templeton, David J.; Grulich, Andrew E.
Abstract : Background: Anal cancer incidence increased markedly in people living with HIV (PLWHIV) after the introduction of HAART, but in a few setting settings, recent declines have been reported. We report the incidence and time trends of anal cancer in PLWHIV in Australia. Study design: A data linkage study between the National HIV Registries and the Australian Cancer Database. Methods: Cases of anal squamous cell carcinoma (ASCC) in Australians aged 16 years and above diagnosed with HIV between 1982 and 2012 were identified. Standardized incidence ratios (SIRs) were calculated to compare incidence with that of the general population. Poisson regression models were developed to describe the time trends of ASCC over time and to compare ASCC risk within subgroups of PLWHIV. Results: Among 28 696 individuals, a total of 129 cases of ASCC were identified. The crude incidence was 36.3 per 100 000 person-years and it increased sharply from 14.8 to 62.1 per 100 000 person-years between 1982–1995 and 2009–2012 ( P trend <0.001). The SIR was 35.3 (95% confidence interval 29.5–42.0), and there was an inverse association between SIR and increasing age ( P trend <0.001). In multivariate analyses, ASCC incidence was significantly higher in recent years ( P trend <0.001), in those who acquired HIV through male homosexual contact ( P = 0.002), and in those who had a history of AIDS ( P < 0.001). Conclusion: PLWHIV in Australia are at markedly higher risk of anal cancer. Unlike in some industrialized countries with a mature HIV epidemic, the incidence of anal cancer is still increasing in this population in Australia.